PEMANFAATAN VERMIKOMPOS UNTUK PRODUKSI BIOMASSA LEGUM PENUTUP TANAH DAN INOKULUM FUNGI MIKORIZA ARBUSKULA - Abimanyu D Nusantara; C Kusmana; I Mansur; L.K Darusman; Soedarmadi Soedarmadi (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[THE USE OF VERMICOMPOST FOR BIOMASS PRODUCTION OF LEGUME COVER CROP AND INOCULUM OF ARBUSCULAR MYCORRHIZAL FUNGUS]. Vermicompost is an organic fertilizer produced through the digestive system and microorganism inside the earthworm gut. Vermicompost is recognized to have positive effects on the plant growth and development of mycorrhizal symbiosis.The study was aimed to determine the optimum size (diameter and weight) of vermicompost for producing biomass of legume cover crop (LCC) and inoculum of arbuscular mycorrhiza fungus (AMF) of G. etunicatum. A glasshouse experiment was arranged in a randomized block design, involving different diameter size and weight of vermicompost as the treatments. Results showed that vermicompost is a potential substitute to inorganic fertilizer for production of LCC biomass and AMF inoculum.Vermicompost applied with diameter < 250 µm weighing 150 – 172 mg produced the highest root dry weight of LCC, root colonization, and number of spores of G. etunicatum. A linear relation was found between root colonization and number of spores of G. etunicatum.